2005
DOI: 10.1007/s00428-005-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings in a patient with Fabry disease who died after 2.5 years of enzyme replacement

Abstract: We describe the postmortem findings of a 47-year-old man with Fabry disease, an X-linked glycolipid storage disorder, who was on enzyme replacement therapy with recombinant α-galactosidase A for more than 2 years. The patient had widespread atherosclerotic coronary artery disease that culminated in a massive acute myocardial infarction. Atherosclerotic lesions were seen in the right and left coronary systems, aorta, and the basilar artery. Typical Fabry cardiomyopathy and glomerular nephropathy were found. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 20 publications
8
77
1
Order By: Relevance
“…This finding is supported by our observation that only vascular endothelial cells were cleared of lipid deposits in a patient who was treated for 2.5 years with the other enzyme preparation (agalsidase beta) [26,27]. It would therefore be important to further study the mechanism of uptake of agalsidase alfa into various cell types and tissues.…”
Section: Discussionsupporting
confidence: 56%
“…This finding is supported by our observation that only vascular endothelial cells were cleared of lipid deposits in a patient who was treated for 2.5 years with the other enzyme preparation (agalsidase beta) [26,27]. It would therefore be important to further study the mechanism of uptake of agalsidase alfa into various cell types and tissues.…”
Section: Discussionsupporting
confidence: 56%
“…Clinically, the disease presents as a vascular disease, with development of cerebral white matter lesions (WMLs), cardiac hypertrophy, and kidney disease. Premature coronary artery and cerebral artery disease were found in one cohort 5 but was not confirmed in other studies. 6,7 A proportion of female carriers with α-galactosidase A deficiency also develop disease, albeit with a more protracted course.…”
contrasting
confidence: 71%
“…In Fabry disease patients, lysoGb3 levels in plasma were measured with a newly developed method based on tandem mass spectrometry with isotope-labeled lysoGb3 (5,6,7,8,9,13C5-lysoGb3) as an internal standard.…”
Section: Laboratory Assessmentsmentioning
confidence: 99%
“…Eng et al (2001b) reported that microvascular endothelial deposits of globotriaosylceramide were remarkably decreased by ERT with agalsidase beta but that no significant difference was observed in regard to improvement in neuropathy between Fabry patients treated with agalsidase beta and those treated with a placebo. Schiffmann et al (2006) reported the autopsy results for a 47-year-old man who was on ERT for more than 2 years before he died. They revealed that repeated infusions with agalsidase beta over a prolonged period did not appreciably remove storage material from tissues, including dorsal root ganglia, other than vascular endothelial cells.…”
Section: Human Fibroblastsmentioning
confidence: 99%